Investigation of Mone 2013 Preschool Education Program in Terms of Brain Based Learning Approach - (:unkn) unknown (T.C. Milli Egitim Bakanligi, 2021)
The skill “easily adapting of brain to the environment in early childhood years” is named as neuroplasticity. Preschool period is seen as an incredibly critical period in terms of neuroplasticity because in this period, brain is an incredibly sensitive for the stimulus in environment. Synaptic connections between neurons in child’s brain are established with positive stimulus given for child and in this way, easier and more lasting learnings realize starting from this. It is thought that educational programs prepared for preschoolers should be aimed at the functional rules and multidevelopment of brain. Therefore, the aim of this study is to investigate the indicators in the MoNE 2013 Pre-School Education Program in terms of brain-based learning approach. In this context, it is tried to determine which parts of the brain the indicators in the program are based on. The research conducted as a case study design. The data were obtained by the means of Brain Parts Control List developed by the researches and consisting of 7 dimension and 19 sub-dimensions. In data analyses, Pearson Correlation and frequency analyses were used. It was found that there is a huge amount of the indicator number activating Broca Area (speaking, expressive language control and motor control) and Dorsal Lateral Cortex (high-level thinking skills). © 2021. All Rights Reserved.
Keywords: Brain Development; Brain Parts; Preschool; Preschool Education Program